Nanoscale cathodoluminescene imaging of III‐nitride‐based LEDs with semipolar quantum wells in a scanning transmission electron microscope. Issue 1 (6th October 2015) - Müller, Marcus; Schmidt, Gordon; Metzner, Sebastian; Veit, Peter; Bertram, Frank; Leute, Robert Anton Richard; Heinz, Dominik; Wang, Junjun; Meisch, Tobias; Scholz, Ferdinand; Christen, Jürgen
Abstract : The optical and crystalline properties of a c‐plane GaN‐based LED structure with embedded semipolar InGaN quantum wells (QW) were investigated using highly spatially resolved cathodoluminescence spectroscopy (CL) directly performed in a scanning transmission electron microscope (STEM). Direct correlation of the cross‐sectional STEM image with the simultaneously recorded spatially resolved CL mapping at room‐temperature reveals the most intense emission coming from the semipolar InGaN QWs. We observe an inhomogeneous wavelength distribution due to local indium fluctuations and varying QW thickness. In contrast, the donor‐acceptor pair recombination (DAP) becomes the dominating luminescence process at 16 K resulting in a superposition of the DAP luminescence and the InGaN QW emission.